Method for producing octacalcium phosphate molded article compounded with biocompatible polymer

JP2023155671A5Active Publication Date: 2025-04-21NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022065131
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-04-11
Publication Date
2025-04-21
Estimated Expiration
2042-04-11

AI Technical Summary

Technical Problem

Existing methods for producing calcium phosphate molded bodies face challenges in maintaining shape and strength due to the inhibitory effects of sodium and ammonium ions in buffer solutions, making it difficult to support drugs effectively.

Method used

A method involving the mixing of compounds containing calcium and phosphate ions with a biocompatible polymer, followed by a reaction to form an octacalcium phosphate molded body, ensuring the polymer is composited within the calcium phosphate structure.

Benefits of technology

The resulting octacalcium phosphate molded body maintains a certain shape and strength, allowing for effective drug support and compatibility with biological environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a method for producing an octacalcium phosphate molded article compounded with a biocompatible polymer.SOLUTION: Provided is a method for producing an octacalcium phosphate molded article compounded with a biocompatible polymer, the method comprising a step for mixing a compound containing calcium ions and a compound containing phosphate ions with a solution containing a biocompatible polymer to produce a mixed soil matter and a step for packing the mixed soil matter into a mold and then reacting the calcium ions with the phosphate ions.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a method for producing a molded octacalcium phosphate body complexed with a biocompatible polymer. [Background technology]

[0002] Calcium phosphate, which induces bone formation and promotes tissue regeneration, is used as a bone filler material for the reconstruction and regeneration of bone defects caused by accidents or disease. Calcium phosphate implanted in the body is designed on the premise that bone replacement occurs through the action of osteoclasts, and that the bone remodeling process (bone metabolism) functions properly through the cooperation of osteoblasts and osteoclasts. However, in patients with rheumatoid arthritis and osteoporosis, which affect millions of people in Japan, the bone remodeling process may not function properly, and therefore bone fillers must be used with caution.

[0003] To improve the functionality of bone fillers, a technique for loading drugs onto a calcium phosphate compound as a base material is known. By loading drugs according to the purpose, it becomes possible to make the material effective even in cases where it is difficult to apply current bone fillers. For example, Patent Document 1 discloses a technique related to calcium phosphate loaded with drugs such as indomethacin, insulin, and aspirin.

[0004] Patent Document 2 discloses a biological hard tissue-like hardened material that can be used in a drug delivery system, which contains a biopolymer such as collagen or hyaluronic acid and a calcium phosphate compound. By combining these biopolymers, the hard and brittle properties characteristic of ceramics can be improved, and flexibility can be imparted. Patent Document 3 discloses a bone regeneration material composed of a composite of octacalcium phosphate particles and gelatin. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 6-228011 [Patent Document 2] Japanese Patent Application Laid-Open No. 2003-93496 [Patent Document 3] International Publication No. 2020 / 071497 Summary of the Invention [Problem to be solved by the invention]

[0006] Calcium phosphate does not refer to a single compound, but rather there are several known types. Calcium phosphates used in medical applications such as bone fillers include calcium hydrogen phosphate dihydrate (DCPD), octacalcium phosphate (OCP), hydroxyapatite (HAp), carbonate apatite (CO3Ap), tricalcium phosphate α-phase (α-TCP), and tricalcium phosphate β-phase (β-TCP). Among these, octacalcium phosphate (OCP) is known to have particularly excellent bone regeneration capabilities.

[0007] Calcium phosphate shaped bodies can be produced by a dissolution-precipitation reaction. Specifically, a compound containing calcium ions is reacted in a weakly basic phosphoric acid solution to induce a dissolution-precipitation reaction, producing a calcium phosphate shaped body. However, this method has the problem that it is difficult to prepare a calcium phosphate shaped body that supports a drug. The drug is supported in the calcium phosphate crystals, but the sodium ions and ammonium ions, which are cations in the buffer solution used in the dissolution-precipitation reaction, strongly inhibit the support of the drug, making it difficult to carry out the dissolution-precipitation reaction. Therefore, it has been difficult to manufacture a molded article that maintains a constant shape and strength.

[0008] In view of these problems, the inventors have conducted extensive research and discovered that by first kneading a biocompatible polymer with a compound containing calcium ions, etc., and then molding the mixture, the calcium ions and phosphate ions are reacted to synthesize octacalcium phosphate, which allows the preparation of a molded product containing a biocompatible polymer that maintains a consistent shape and strength, leading to the present invention. Based on this discovery, the present invention aims to provide a method for producing a molded product containing a biocompatible polymer. [Means for solving the problem]

[0009] One aspect of the present invention that can solve the above problems is as follows. [1] A method for producing a biocompatible polymer-composite octacalcium phosphate molded body, comprising the steps of: mixing a compound containing calcium ions and a compound containing phosphate ions with a solution containing a biocompatible polymer to form a mixed mud; and filling the mixed mud into a mold to react the calcium ions and phosphate ions. [2] A method for producing a molded octacalcium phosphate body complexed with a biocompatible polymer, the method comprising the steps of: mixing a compound containing calcium ions with a solution containing a biocompatible polymer to prepare a mixed mud; adding a compound containing phosphate ions to the mixed mud and mixing the mixed mud; and filling the resulting mixed mud into a mold to react the calcium ions with the phosphate ions. [3] A method for producing a biocompatible polymer-composite octacalcium phosphate molded body, comprising the steps of: mixing a compound containing calcium ions with a solution containing a biocompatible polymer to form a mixed mud; filling the mixed mud into a mold and then freezing it; and immersing the molded body obtained by the freezing in a solution of a compound containing phosphate ions to react the calcium ions with the phosphate ions. [4] The method for producing an octacalcium phosphate molded product complexed with a biocompatible polymer according to any one of [1] to [3], wherein the calcium ion-containing compound is at least one selected from the group consisting of calcium dihydrogen phosphate hydrate, calcium dihydrogen phosphate anhydrate, calcium hydrogen phosphate dihydrate, calcium hydrogen phosphate anhydrate, hydroxyapatite, carbonate apatite, sodium-substituted hydroxyapatite, tricalcium phosphate α-phase, tricalcium phosphate β-phase, and calcium carbonate. [5] The method for producing an octacalcium phosphate molded product complexed with a biocompatible polymer according to any one of [1] to [3], wherein the compound containing phosphate ions is one or more selected from the group consisting of sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, and magnesium ammonium phosphate. [6] A method for producing a biocompatible polymer-composite octacalcium phosphate molded body according to any one of [1] to [4], wherein the biocompatible polymer is one or more selected from the group consisting of alginic acid, gelatin, hyaluronic acid, gellan gum, carboxylic acid-modified cellulose, sodium polyacrylate, polyethylene glycol, pullulan, phosphorylated pullulan, polyglutamic acid, fibrin, chitin, chitosan, and gellan gum. [Effects of the Invention]

[0010] The present invention provides a method for producing octacalcium phosphate molded articles composited with a biocompatible polymer, which have the excellent effect of maintaining a consistent shape and strength. [Brief explanation of the drawings]

[0011] [Figure 1] 1 is a photograph of a molded body produced in Example 1 (a photograph substituting for a drawing). [Figure 2] FIG. 2 is a diagram showing the results of XRD analysis of the molded body produced in Example 1. [Figure 3] 1 is a SEM photograph of the molded body produced in Example 1 (a photograph substituting for a drawing). [Figure 4] 1 is a photograph of a molded body produced in Example 2 (a photograph substituting for a drawing). [Figure 5] FIG. 1 is a diagram showing the results of XRD analysis of the molded body produced in Example 2. [Figure 6] 1 shows the results of measuring the DTS strength of the molded body produced in Example 2. [Figure 7] FIG. 1 is a diagram showing a stress-strain curve of the molded body produced in Example 2. [Figure 8] 1 is a SEM photograph (a photograph substituting for a drawing) of the molded body produced in Example 2. [Figure 9] 1 is a photograph of a molded body produced in Example 3 (a photograph substituting for a drawing). [Figure 10] FIG. 1 is a diagram showing the results of XRD analysis of the molded body produced in Example 3. [Figure 11] 1 shows the results of measuring the DTS strength of the molded body produced in Example 3. [Figure 12] FIG. 10 is a diagram showing a stress-strain curve of the molded body produced in Example 3. [Figure 13] 1 is a photograph of a molded body produced in Example 4 (a photograph substituting for a drawing). [Figure 14] 1 shows the results of measuring the DTS strength of the molded body produced in Example 4. [Figure 15] FIG. 10 is a diagram showing the stress-strain curve of the molded body produced in Example 4. [Figure 16] FIG. 10 is a diagram showing the results of XRD analysis of the molded body produced in Example 4. [Figure 17] 1 shows photographs of the molded bodies produced in Examples 5 and 6 (photographs used as drawing substitutes). [Figure 18] FIG. 1 shows the results of XRD analysis of the molded bodies produced in Examples 5 and 6. [Figure 19] 1 shows the results of measuring the DTS strength of the molded bodies produced in Examples 5 and 6. [Figure 20] 1 is a photograph of a molded body produced in Example 7 (a photograph substituting for a drawing). [Figure 21] FIG. 10 is a diagram showing the results of XRD analysis of the molded body produced in Example 7. [Figure 22] 1 is a SEM photograph (a photograph substituting for a drawing) of the molded body produced in Example 7. [Figure 23] 1 is a photograph of a molded body produced in Example 8 (a photograph substituting for a drawing). [Figure 24] 1 is a CT image of the molded body produced in Example 8 (photograph as a substitute for a drawing). [Figure 25] FIG. 10 is a diagram showing the results of XRD analysis of the molded body produced in Example 8. DETAILED DESCRIPTION OF THE INVENTION

[0012] The present invention will be described in detail below. The following description is an example (typical example) of an embodiment of the present invention, and the present invention is not limited to these contents and can be practiced in various modifications within the scope of the gist thereof.

[0013] The molded article obtained by an embodiment of the present invention is a molded article mainly composed of octacalcium phosphate (OCP) complexed with a biocompatible polymer, and can primarily contribute to the bone remodeling process. By reacting calcium ions with phosphate ions in the presence of a biocompatible polymer, a molded article complexed with a biocompatible polymer can be obtained during the crystal growth process of octacalcium phosphate (OCP). The complexation causes the crystals to become entangled or fused, which allows the molded article to maintain its shape as a whole, and it can maintain its shape to the extent that it does not collapse even when immersed in solutions such as distilled water or ethanol.

[0014] [1] First embodiment The first embodiment is a method for producing an octacalcium phosphate molded body complexed with a biocompatible polymer, the method comprising the steps of: mixing a compound containing calcium ions and a compound containing phosphate ions with a solution containing a biocompatible polymer to form a mixed mud; and filling the mixed mud into a mold to react the calcium ions and phosphate ions.

[0015] In the first embodiment, calcium phosphate (excluding octacalcium phosphate) can be used as the compound containing calcium ions, and examples thereof include calcium dihydrogen phosphate hydrate, calcium dihydrogen phosphate anhydrate, calcium hydrogen phosphate dihydrate, calcium hydrogen phosphate anhydrate, hydroxyapatite, carbonate apatite, sodium-substituted hydroxyapatite, tricalcium phosphate α-phase, and tricalcium phosphate β-phase. These may be used alone or in combination in any ratio.

[0016] In addition to the calcium phosphate, other calcium ion-containing compounds may include inorganic calcium salts or organic calcium salts. Examples of inorganic calcium salts include calcium carbonate, calcium hydroxide, calcium oxide, calcium chloride, calcium fluoride, calcium bromide, calcium iodide, calcium phosphide, calcium sulfate, calcium sulfate hemihydrate, calcium sulfate dihydrate, calcium oxalate anhydrate, calcium oxalate monohydrate, calcium oxalate dihydrate, calcium oxalate trihydrate, calcium sulfite, calcium silicate, calcium pyrophosphate, calcium tungstate, and calcium molybdate. Examples of organic calcium salts include calcium acetate, calcium succinate, calcium citrate, calcium malate, calcium thiomalate, calcium benzoate, calcium lactate, and calcium stearate. These salts may be used alone or in combination in any desired ratio.

[0017] In the first embodiment, examples of the compound containing phosphate ions include sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium magnesium phosphate, magnesium phosphate, etc. Any of these may be used alone or in combination.

[0018] Generally, biocompatible polymers are materials that are intended to be implanted in the body without being rejected or recognized as foreign bodies and / or have biocompatible properties, and are absorbed by the body over time. For therapeutic purposes, such biocompatible polymers can be used as drugs. It is desirable for them to have affinity with the body, such as appropriate solubility in the body and the ability to form bonds with calcium salts. Because biocompatible polymers must be composited with molded bodies primarily composed of octacalcium phosphate, it is desirable for them to be able to impart flexibility and toughness, which can improve the formability and mechanical properties of the molded bodies.

[0019] In this specification, the term "biophilic polymer" refers to a molecule having a molecular weight of more than 400 and having a structure formed by a large number of repeating units substantially or conceptually derived from molecules with a smaller molecular weight. Specifically, the term "biophilic polymer" includes those classified into linear polymers, star polymers, comb polymers, brush polymers, two-dimensional polymers, three-dimensional polymers, etc., based on the state of polymerization and the state of regular structure of the polymer. These polymers may contain other structures in the side chains or repeating units, or may contain a rotaxane structure, etc.

[0020] There are a wide variety of biocompatible polymers, and the polymers to be composited are not particularly limited, but examples include alginate, gelatin, collagen, actin, fibrin, starch, dextrin, amylose, amylopectin, pectin, glycogen, curdlan, paramylon, agarose, carrageenan, heparin, xyloglucan, glucomannan, levan, fructan, pullulan, phosphorylated pullulan, fibroin, cellulose, chitosan, chitin, polyglycolic acid, polylactic acid, polyglycolic acid-polylactic acid copolymer, poly-L-lactic acid, melanin, hyaluronic acid, gellan gum, mastic gum, carboxylic acid-modified cellulose, lignin, casein, polyglutamic acid, sodium polyacrylate, and polyethylene glycol. These can be used alone or in combination.

[0021] In this specification, a solution containing a biocompatible polymer can be prepared by dissolving the biocompatible polymer in a solvent. The solvent is not particularly limited and is usually in the form of water or an aqueous solution, but other solvents can also be used. When a solvent other than water is used, it must be liquid under the reaction temperature and pressure conditions. For example, methanol, ethanol, propan-1-ol, butan-1-ol, pentan-1-ol, hexane-1-ol, heptane Primary alcohols such as 2-propanol (isopropyl alcohol), butan-2-ol, pentan-2-ol, hexane-2-ol, cyclohexanol, etc.; monohydric alcohols including tertiary alcohols such as tert-butyl alcohol, 2-methylbutan-2-ol, 2-methylpentan-2-ol, 2-methylhexane-2-ol, 3-methylpentan-3-ol, 3-methyloctan-3-ol; dihydric alcohols such as ethylene glycol and diethylene glycol; trihydric alcohols such as glycerin; aromatic alcohols such as phenol; polyethers such as polyethylene glycol (PEG) and polypropylene glycol (PPG); Examples of suitable amine compounds include fatty acids such as acetic acid, valeric acid, caproic acid, lauric acid, palmitic acid, stearic acid, oleic acid, and linoleic acid, alkanes such as pentane, butane, hexane, septane, and octane, esters such as ethyl acetate, methyl butyrate, methyl salicylate, ethyl formate, ethyl butyrate, ethyl caproate, octyl acetate, and dibutyl phthalate, compounds known as cycloalkanes or bicycloalkanes such as cyclopentane, cyclohexane, and decalin, ketones such as acetone, methyl ethyl ketone, and diethyl ketone, aldehydes such as formaldehyde, acetaldehyde, propionaldehyde, butanal, pentanal, hexanal, and vanillin, and amine compounds such as aminomethane, aminoethane, ethylenediamine, triethylamine, and aniline. These compounds may be used alone or in combination.

[0022] In the first embodiment, a mixed mud is prepared by mixing a compound containing calcium ions and a compound containing phosphate ions with a solution containing a biocompatible polymer. The mixing method is not particularly limited, but for example, a solution containing a biocompatible polymer can be added dropwise to a mixed powder of a compound containing calcium ions and a compound containing phosphate ions, and the resulting mixture can be thoroughly mixed using a spatula or the like to prepare the mixed mud. The mixing ratio, in terms of weight ratio of the mixed powder of a compound containing calcium ions and a compound containing phosphate ions to the biocompatible polymer, is preferably 200:1 to 1:1. It is more preferably 100:1 to 2:1, even more preferably 50:1 to 3:1, and particularly preferably 20:1 to 5:1.

[0023] The resulting mixed mud is then filled into a mold, sealed, and cured. The curing temperature and curing time can be set as appropriate, and the curing temperature can be, for example, 5 to 95°C, preferably 15 to 80°C. The curing time can be, for example, 2 to 96 hours, preferably 6 to 72 hours. During this curing process (the process in which calcium ions and phosphate ions react), calcium phosphate crystals complexed with a biocompatible polymer are precipitated. After curing, the product is dried using a dryer or the like, and then the molded product is removed from the mold. If unreacted components remain after removal, they are preferably washed and removed using distilled water or the like. In this manner, a biocompatible polymer-complexed octacalcium phosphate molded product can be produced.

[0024] [2] Second embodiment The second embodiment is a method for producing an octacalcium phosphate molded body complexed with a biocompatible polymer, which includes the steps of: mixing a compound containing calcium ions with a solution containing a biocompatible polymer to form a mixed mud; adding a compound containing phosphate ions to the mixed mud and mixing them; and filling the resulting mixed mud into a mold to react the calcium ions with the phosphate ions.

[0025] In the second embodiment, for example, calcium inorganic salts or calcium organic salts can be used as the compound containing calcium ions. Examples of inorganic salts of calcium include calcium carbonate, calcium hydroxide, calcium oxide, calcium chloride, calcium fluoride, calcium bromide, calcium iodide, calcium phosphide, calcium sulfate, and calcium sulfate. Examples of calcium salts include calcium hemihydrate, calcium sulfate dihydrate, anhydrous calcium oxalate, calcium oxalate monohydrate, calcium oxalate dihydrate, calcium oxalate trihydrate, calcium sulfite, calcium silicate, calcium pyrophosphate, calcium tungstate, and calcium molybdate. Examples of calcium organic salts include calcium acetate, calcium succinate, calcium citrate, calcium malate, calcium thiomalate, calcium benzoate, calcium lactate, and calcium stearate. These may be used alone or in combination in any desired ratio.

[0026] In addition to the above inorganic calcium salts or organic calcium salts, calcium phosphates (excluding octacalcium phosphate) can also be used as calcium ion-containing compounds, such as calcium dihydrogen phosphate hydrate, calcium dihydrogen phosphate anhydrate, calcium hydrogen phosphate dihydrate, calcium hydrogen phosphate anhydrate, hydroxyapatite, carbonate apatite, sodium-substituted hydroxyapatite, tricalcium phosphate α-phase, and tricalcium phosphate β-phase. These may be used alone or in combination in any desired ratio.

[0027] A solution containing an inorganic salt of phosphoric acid can be used as the solution of a compound containing phosphate ions. Examples of inorganic salts of phosphoric acid include sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, and magnesium ammonium phosphate. These may be used alone or in combination in any desired ratio.

[0028] In the second embodiment, a compound containing calcium ions is mixed with a solution containing a biocompatible polymer. The mixing ratio, by weight, of the compound containing calcium ions to the biocompatible polymer is preferably 200:1 to 1:1. It is more preferably 100:1 to 2:1, even more preferably 50:1 to 3:1, and particularly preferably 20:1 to 5:1. There are no particular limitations on the mixing method; for example, a solution containing a biocompatible polymer is added dropwise to a compound (powder) containing calcium ions, and the two are thoroughly mixed using a spatula or the like. For example, a mixed mud is prepared by mixing calcium carbonate powder, the raw material, with a solution containing a biocompatible polymer obtained by dissolving the biocompatible polymer in a solvent.

[0029] Next, a solution of a compound containing phosphate ions is mixed into the mixed mud. This causes, for example, calcium carbonate contained in the mixed mud to react with phosphoric acid in the solution to form octacalcium phosphate. Vigorous foaming and partial hardening may occur during the reaction, but it is preferable to continue mixing until the foaming reaction settles down. The ratio of each compound can be adjusted so that calcium ions and phosphate ions react to form octacalcium phosphate.

[0030] Next, the resulting mixed mud is filled into a mold, sealed, and cured. The curing temperature and curing time can be set as appropriate; for example, the curing temperature can be 35 to 50°C, and the curing time can be 10 minutes to 96 hours. During this curing process (the process in which calcium ions and phosphate ions react), crystals of octacalcium phosphate containing a biocompatible polymer are precipitated. After curing, the mixture is dried using a dryer or the like, and the molded product is then removed from the mold. If any unreacted components remain after removal, they are preferably washed and removed using distilled water or the like. In this manner, a molded product of octacalcium phosphate complexed with a biocompatible polymer can be produced.

[0031] [3] Third embodiment The third embodiment includes a step of mixing a compound containing calcium ions with a solution containing a biocompatible polymer to prepare a mixed mud, a step of filling the mixed mud into a mold and then freezing the mold, and a step of freezing the frozen mixture. and immersing the sintered shaped body in a solution of a compound containing phosphate ions to cause a reaction between the calcium ions and the phosphate ions.

[0032] In the third embodiment, calcium phosphate (excluding octacalcium phosphate) can be used as the compound containing calcium ions, and examples thereof include calcium dihydrogen phosphate hydrate, calcium dihydrogen phosphate anhydrous, calcium hydrogen phosphate dihydrate, calcium hydrogen phosphate anhydrous, hydroxyapatite, carbonate apatite, sodium-substituted hydroxyapatite, tricalcium phosphate α-phase, and tricalcium phosphate β-phase.

[0033] In addition to calcium phosphate, inorganic calcium salts or organic calcium salts can also be used as calcium ion-containing compounds. Examples of inorganic calcium salts include calcium carbonate, calcium hydroxide, calcium oxide, calcium chloride, calcium fluoride, calcium bromide, calcium iodide, calcium phosphide, calcium sulfate, calcium sulfate hemihydrate, calcium sulfate dihydrate, calcium oxalate anhydrate, calcium oxalate monohydrate, calcium oxalate dihydrate, calcium oxalate trihydrate, calcium sulfite, calcium silicate, calcium pyrophosphate, calcium tungstate, and calcium molybdate. Examples of organic calcium salts include calcium acetate, calcium succinate, calcium citrate, calcium malate, calcium thiomalate, calcium benzoate, calcium lactate, and calcium stearate. These salts may be used alone or in combination in any desired ratio.

[0034] In the third embodiment, a solution containing an inorganic salt of phosphoric acid can be used as the solution of a compound containing phosphate ions. Examples of inorganic salts of phosphoric acid include sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, and magnesium ammonium phosphate. These may be used alone or in combination in any ratio.

[0035] In the third embodiment, a compound containing calcium ions is mixed with a solution containing a biocompatible polymer to form a mixed mud, and then the mixed mud is filled into a mold. For example, calcium carbonate powder is prepared as a raw material, and a solution containing the biocompatible polymer obtained by dissolving the biocompatible polymer in a solvent is mixed with the raw material powder to form the mixed mud. The mixing ratio, in terms of weight ratio of the compound containing calcium ions to the biocompatible polymer, is preferably 200:1 to 1:1. A more preferred range is 100:1 to 2:1, even more preferred is 50:1 to 3:1, and particularly preferred is 20:1 to 5:1.

[0036] Next, this mixed mud is filled into a mold and then frozen. The freezing temperature is preferably −15°C or lower. While there is no particular lower limit, it is preferably −50°C or higher. After freezing, the frozen state is dried (lyophilized) to remove moisture. After freezing (preferably after lyophilization), the molded body is removed from the mold and immediately immersed in a solution of a compound containing phosphate ions. This causes the calcium ions and phosphate ions to react with each other, changes the state of the biocompatible polymer, insolubilizes it, and maintains its shape. The immersion temperature and immersion time can be set appropriately, and the immersion temperature can be, for example, 50 to 70°C. The immersion time can be, for example, 10 minutes to 96 hours. During this immersion process, the frozen molded body dissolves, but at the same time, calcium phosphate crystals containing the biocompatible polymer precipitate, maintaining its shape. In this manner, a biocompatible polymer-complexed octacalcium phosphate molded body can be produced.

[0037] (Octacalcium phosphate compact) The molded articles obtained according to the first to third embodiments can achieve a DTS strength of 0.1 MPa or more, 0.3 MPa or more, or even 0.5 MPa or more. If the DTS strength is 0.1 MPa or more, the article will not collapse even when pinched firmly with tweezers, and can be easily transplanted into a bone defect in a living body. However, in consideration of ease of operation, a higher strength is preferable.

[0038] The shape of the mold basically depends on the shape of the mold used to fill the mixed mud, but since it has a certain strength, it can be processed into specific shapes. For example, it can be processed into cubes, rectangular parallelepipeds, cylinders, cones, truncated cones, spheres, octahedrons, tetrahedrons, etc. The volume of the molded product is 1mm 3 More than 3mm 3 Above, especially 5mm 3 On the other hand, 1000mm 3 If the temperature exceeds this range, there is a concern that the strength may decrease. [Example]

[0039] The following description will be given based on examples. Note that these examples are merely examples and are not intended to limit the scope of the present invention. That is, the present invention is limited only by the scope of the claims, and includes various modifications other than the examples included in the present invention.

[0040] The physical properties of the molded body were evaluated using the following measuring devices and conditions. (About DTS strength) The diametral tensile strength (DTS strength) was measured using a Shimadzu Corporation universal testing machine, AGS-J, at a head speed of 1 mm / min.

[0041] (About X-ray diffraction analysis) XRD analysis was performed using an X-ray diffraction analyzer (MiniFlex600, Rigaku Corporation, Japan, target: Cu, wavelength: 0.15406 nm). The XRD measurement conditions were an acceleration voltage of 40 kV and amplitude of 15 mA, respectively. For characterization, the diffraction angle was continuously scanned at 2θ values ​​from 3° to 70° at a scanning speed of 2° / min. When the molded body was analyzed by X-ray diffraction, the formation of OCP was confirmed by evaluating the peaks of octacalcium phosphate in addition to the peaks of the biocompatible polymer.

[0042] (Stress-strain curve) The stress-strain curve was measured using a Shimadzu Corporation universal testing machine, AGS-J, at a head speed of 1 mm / min.

[0043] (Electron microscope observation) The microstructure of the samples was evaluated using a field emission scanning electron microscope (FE-SEM: JSM-6700F, JEOL Ltd., Japan). The accelerating voltage was set to 5 kV, and the samples were sputter-coated with Os to prevent charge accumulation on the surface.

[0044] (FT-IR analysis) Fourier transform infrared spectroscopy (FT-IR: Nicolet NEXUS670, Thermo Fisher Scientific, USA) was performed using a triglycine sulfate detector (32 scans, 2 cm resolution) with an attenuated total reflection prism made of GeSe. -1 ) was used to characterize the chemical oscillation scheme of the sample. The atmosphere was considered as the background for performing the measurements.

[0045] (About micro-CT analysis) The internal microstructure of the sample was evaluated using a micro-CT analyzer (micro-CT: Skyscan1085, Toyo Corporation). The accelerating voltage was set to 60 kV, and an Al filter was used. The evaluation was performed using a resolution of 9 μm.

[0046] Example 1: Alginate-OCP molded body 2.40 g of calcium hydrogen phosphate dihydrate (DCPD) and 2.84 g of disodium hydrogen phosphate (NaAP) were mixed in an automatic agate mortar for at least 10 minutes at 100 rpm to obtain a mixed powder. The mixed powder was placed in a polystyrene tray, and a 50 g / L aqueous solution of ammonium alginate was added dropwise at a water-to-water ratio of 1.0. The mixture was thoroughly mixed with a spatula to obtain a mixed mud, which was then filled into a 6 mm diameter, 3 mm thick silicone mold and cured at 40°C in a sealed state for 3 days. After curing, the mixture was air-dried at 40°C for at least 12 hours, and then removed from the mold. The mixture was then thoroughly washed with distilled water to remove any remaining unreacted components, and then dried again at 40°C.

[0047] Figure 1 shows a photograph of the obtained green body. From Figure 1, it can be seen that the green body maintained the shape of the mold. The DTS strength of this green body was 0.18 ± 0.04 MPa, and it was strong enough that it would not collapse even when pinched with tweezers. Figure 2 shows the results of XRD analysis of this green body. From Figure 2, it was found that the green body obtained was a single phase of octacalcium phosphate (OCP). A portion of the green body was cut out, and the fracture surface was observed with FE-SEM. Figure 3 shows the results. On the cross section, it was observed that scale-like crystals about tens of nanometers in size were densely accumulated, with some of them fused together. In addition, fibrous structures were observed between some of the crystals.

[0048] (Example 2) Gelatin-OCP molded body 2.40 g of calcium hydrogen phosphate dihydrate (DCPD) and 2.84 g of disodium hydrogen phosphate (NaAP) were mixed in an automatic agate mortar for at least 10 minutes at 100 rpm to obtain a mixed powder. The mixed powder was placed in a polystyrene tray, and gelatin aqueous solutions (concentrations: 10, 50, and 100 g / L) were added dropwise at a water-to-water ratio of 1.0. The mixture was thoroughly mixed with a spatula to obtain a mixed mud, which was then filled into a 6 mm diameter, 3 mm thick silicone mold and cured at 40°C in a sealed state for 3 days. After curing, the mixture was air-dried at 40°C for at least 12 hours, and then removed from the mold. The mixture was then thoroughly washed with distilled water to remove any remaining unreacted components, and again dried at 40°C.

[0049] Figure 4 shows a photograph of the obtained compact. It can be seen from Figure 4 that the compact maintained the shape of the mold. Figure 5 shows the XRD analysis results of the compact. It can be seen from Figure 5 that the obtained compact is a single phase of octacalcium phosphate (OCP). Figure 6 shows the DTS strength measurement results. The DTS strength of all the compacts was 0.18 ± 0.04 MPa or higher, indicating that they did not collapse even when pinched with tweezers. Figure 7 shows the stress-strain curve of the compact, indicating that the compact did not collapse even when subjected to a certain strain. A portion of the compact was cut out, and the fracture surface was observed with FE-SEM. Figure 8 shows the results. The cross section showed dense accumulation of scale-like crystals measuring several tens of nanometers, some of which had fused together. Furthermore, fibrous structures were observed between the crystals.

[0050] (Example 3) Sodium polyacrylate-OCP molded body 2.40 g of calcium hydrogen phosphate dihydrate (DCPD) and 2.84 g of disodium hydrogen phosphate (NaAP) were mixed in an automatic agate mortar for at least 10 minutes at 100 rpm to produce a mixed powder. The mixed powder was placed in a polystyrene tray, and a 100 g / L aqueous solution of sodium polyacrylate (PAA-Na) was added dropwise at a water-to-water ratio of 1.0. The mixture was thoroughly mixed with a spatula to produce a mixed mud, which was then filled into a 6 mm diameter, 3 mm thick silicone mold and cured in a sealed state at 40°C for 3 days. After curing, the mixture was air-dried at 40°C for at least 12 hours, and the dried mixed mud was then removed from the mold.

[0051] Figure 9 (left) shows the molded body composited with PAA-Na and the molded body composited with PEG. A photograph of the molded body is shown in Figure 9 (left). Figure 9 (left) shows that the molded body maintains the shape of the mold. Figure 10 shows the XRD analysis results of the molded body (PAA-Na-100g / L). Figure 10 shows that the obtained molded body is a single phase of octacalcium phosphate (OCP). Figure 11 shows the DTS strength (PAA-Na) of the molded body. The DTS strength of all the molded bodies was 0.18±0.04MPa or higher, and they were strong enough not to collapse even when pinched with tweezers. Figure 12 shows the stress-strain curve (PAA-Na) of the molded body, and it can be seen that the molded body did not show any significant fracture strength but showed high plastic deformation. In other words, the molded body was soft.

[0052] (Example 4) Polyethylene glycol-OCP molded body 2.40 g of calcium hydrogen phosphate dihydrate (DCPD) and 2.84 g of disodium hydrogen phosphate (NaAP) were mixed in an automatic agate mortar for at least 10 minutes at 100 rpm to produce a mixed powder. The mixed powder was placed in a polystyrene tray, and a 100 g / L polyethylene glycol (PEG) aqueous solution was added dropwise to the tray at a water-to-water ratio of 1.0. The mixture was thoroughly mixed with a spatula to produce a mixed mud, which was then filled into a 6 mm diameter, 3 mm thick silicone mold and cured in a sealed state at 40°C for 3 days. After curing, the mixture was air-dried at 40°C for at least 12 hours, and the dried mixed mud was then removed from the mold.

[0053] Figure 9 (right) shows photographs of the compacts composited with PAA-Na and PEG. Figure 9 (right) shows that the compacts maintained the shape of the mold. Figure 10 shows the XRD analysis results of the compacts (PEG-100g / L). Figure 10 shows that the compacts obtained were composed of a single phase of octacalcium phosphate (OCP). Figure 11 shows the DTS strength (PEG) of the compacts. The DTS strength of all the compacts was 0.18±0.04MPa or higher, which was strong enough that they would not crumble even when pinched with tweezers. Figure 12 shows the stress-strain curve (PEG) of the compacts. It can be seen that the compacts did not exhibit significant fracture strength but exhibited high plastic deformation. In other words, they were soft compacts.

[0054] (Example 5) Gelatin-OCP molded body 1.75 g of calcium carbonate was placed in an agate mortar, and gelatin aqueous solutions (concentrations of 10 g / L and 100 g / L) were added dropwise at a water-to-water ratio of 1.0, and mixed thoroughly to form a slurry. 2 mL of 4 mol / L phosphoric acid aqueous solution was added dropwise to this slurry, and the mixture was quickly stirred with a pestle to form a mixed mud. Vigorous foaming occurred during mixing, and the mixture partially hardened, but the mixture was stirred until it settled. This mixed mud was filled into a 6 mm diameter, 3 mm thick silicone mold and cured at 40°C in a sealed state for 3 days. After curing, the mixture was air-dried at 40°C for at least 12 hours, and then removed from the mold. It was then washed with distilled water and dried.

[0055] Figure 13 shows a photograph of the obtained compacts. From Figure 13, it can be seen that the compacts maintained the shape of the mold. Figure 14 shows the DTS strength of the compacts. The DTS strength of all the compacts was 0.18 ± 0.04 MPa or higher, and they were strong enough that they would not crumble even when pinched with tweezers. Figure 15 shows the stress-strain curve of the compacts, which shows that the compacts did not exhibit significant fracture strength but exhibited high plastic deformation. Figure 16 shows the results of XRD analysis of the compacts. From Figure 16, it can be seen that the compacts obtained consisted of a single phase of octacalcium phosphate (OCP).

[0056] (Example 6) Sodium polyacrylate-OCP molded body 1.75 g of calcium carbonate was placed in an agate mortar, and 1 mL of a 10 g / L aqueous solution of sodium polyacrylate (PAA-Na) was added dropwise and mixed thoroughly to form a slurry. 2 mL of a 4 mol / L aqueous solution of phosphoric acid was added dropwise to this slurry, and the mixture was quickly stirred with a pestle to form a mixed mud. Vigorous foaming occurred during mixing, and the mixture partially hardened, but this The mixture was stirred until it settled. This mixed mud was filled into a silicone mold with a diameter of 6 mm and a thickness of 3 mm, and cured in a sealed state at 40°C for 3 days. After curing, the mixture was dried at 40°C for more than 12 hours, and then removed from the mold. It was then washed with distilled water and dried.

[0057] A photograph of the obtained compact is shown in Figure 17. It can be seen from Figure 17 that the compact maintained the shape of the mold. The XRD pattern of the compact is shown in Figure 18, and the DTS strength is shown in Figure 19. The DTS strength of the compact was 0.88 ± 0.04 MPa or more, and it was strong enough that it would not collapse even when pinched with tweezers.

[0058] (Example 7) Alginate-OCP molded body A mixed mud was prepared by mixing 1 g of calcium hydrogen phosphate dihydrate (DCPD) with a 50 g / L aqueous solution of ammonium alginate at a water-to-water ratio of 1.0. This mixed mud was filled into a silicon mold with a diameter of 6 mm and a thickness of 3 mm, frozen at -20°C, and then dried in a freeze dryer to remove the water. The molded body after drying maintained the shape of the mold. The molded body was then immersed in 20 mL of a 1 mol / L aqueous solution of disodium hydrogen phosphate (NaAP) and reacted at 60°C for 1 day. The molded body foamed during the reaction, but maintained its shape.

[0059] Figure 20 shows photographs of the molded body before and after immersion. From Figure 20, it can be seen that the molded body maintained the shape of the mold even after immersion. Pores of several hundred microns were observed due to the formation of ice crystals during freezing. The DTS strength of the molded body was 0.54 ± 0.21 MPa or higher. Figure 21 shows the results of XRD analysis of the molded body after immersion. From Figure 21, it was observed that octacalcium phosphate (OCP) had formed in some parts of the molded body. Figure 22 shows an SEM image of the molded body after immersion. Radial OCP crystals were observed embedded within the alginate fibers.

[0060] (Example 8) Alginate-OCP molded body 1 g of calcium carbonate and a 50 g / L aqueous solution of ammonium alginate were mixed at a water-to-water ratio of 1.0 to prepare a mixed mud. This mixed mud was filled into a silicon mold with a diameter of 6 mm and a thickness of 3 mm, frozen at -20°C, and then dried in a freeze dryer to remove the water. The molded body after drying maintained the shape of the mold. The molded body was then immersed in 20 mL of 100 mol / L phosphoric acid and reacted at 60°C for 3 days. The molded body foamed during the reaction, but maintained its shape.

[0061] Figure 23 shows photographs of the green body before and after immersion. From Figure 23, it can be seen that the green body maintained the shape of the mold even after immersion. Figure 24 shows a CT image of the green body. Pores of several hundred microns were observed due to the formation of ice crystals during freezing. The DTS strength of the green body was 0.32 ± 0.12 MPa. Figure 25 shows the results of XRD analysis of the green body after immersion. From Figure 25, it was observed that octacalcium phosphate (OCP) had formed in some parts of the green body.

Claims

1. A method for producing an octacalcium phosphate molded body complexed with a biocompatible polymer, comprising the steps of: mixing a compound containing calcium ions and a compound containing phosphate ions with a solution containing a biocompatible polymer to obtain a mixed mud; filling the mixed mud into a mold and curing it at 15°C to 50°C to cause a reaction between the calcium ions and the phosphate ions.

2. A method for producing an octacalcium phosphate molded body complexed with a biocompatible polymer having a diametral tensile strength (DTS strength) of 0.1 MPa or more, comprising the steps of mixing a compound containing calcium ions and a compound containing phosphate ions with a solution containing a biocompatible polymer to obtain a mixed mud, and filling the mixed mud into a mold and reacting the calcium ions and phosphate ions.

3. A method for producing a molded body of octacalcium phosphate composited with a biocompatible polymer, comprising the steps of: mixing a compound containing calcium ions with a solution containing a biocompatible polymer to obtain a mixed mud; adding a solution of a compound containing phosphate ions to the mixed mud and mixing the mixed mud; and filling the mixed mud obtained after mixing into a mold and curing it at 15°C to 50°C to react the calcium ions with phosphate ions.

4. A method for producing an octacalcium phosphate molding complexed with a biocompatible polymer having a diametral tensile strength (DTS strength) of 0.1 MPa or more, comprising the steps of mixing a compound containing calcium ions with a solution containing a biocompatible polymer to obtain a mixed mud, adding a solution of a compound containing phosphate ions to the mixed mud and mixing it, and filling the mixed mud obtained after mixing into a mold to react the calcium ions with phosphate ions.

5. A method for producing an octacalcium phosphate molded body complexed with a biocompatible polymer, comprising the steps of: mixing a compound containing calcium ions with a solution containing a biocompatible polymer to obtain a mixed mud; filling the mixed mud into a mold and then freezing it; and immersing the molded body obtained by the freezing in a solution of a compound containing phosphate ions to react with the calcium ions and phosphate ions.

6. A process for mixing a compound containing calcium ions with a solution containing a biocompatible polymer to obtain a mixed mud, a process for filling the mixed mud into a mold and then freezing the mold, and a product obtained by the freezing. A method for producing an octacalcium phosphate molded body complexed with a biocompatible polymer having a diametral tensile strength (DTS strength) of 0.1 MPa or more, comprising the steps of: immersing a molded body in a solution of a compound containing phosphate ions to react the calcium ions and phosphate ions.

7. The method for producing an octacalcium phosphate molded product composited with a biocompatible polymer according to any one of claims 1 to 6, wherein the compound containing calcium ions is at least one selected from the group consisting of calcium dihydrogen phosphate hydrate, calcium dihydrogen phosphate anhydrate, calcium hydrogen phosphate dihydrate, calcium hydrogen phosphate anhydrate, hydroxyapatite, carbonate apatite, sodium-substituted hydroxyapatite, tricalcium phosphate α-phase, tricalcium phosphate β-phase, and calcium carbonate.

8. The method for producing an octacalcium phosphate molded product complexed with a biocompatible polymer according to any one of claims 1 to 6, wherein the compound containing phosphate ions is at least one selected from the group consisting of sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, and magnesium ammonium phosphate.

9. The method for producing a shaped product of octacalcium phosphate composited with a biocompatible polymer according to any one of claims 1 to 6, wherein the biocompatible polymer is one or more of alginic acid, gelatin, hyaluronic acid, carboxylate-modified cellulose, sodium polyacrylate, polyethylene glycol, pullulan, phosphorylated pullulan, polyglutamic acid, fibrin, chitin, chitosan, and gellan gum.